Preoperative Visualization of the Artery of Adamkiewicz by Intra-Arterial CT Angiography - Uotani, K.; Yamada, N.; Kono, A.K.; Taniguchi, T.; Sugimoto, K.; Fujii, M.; Kitagawa, A.; Okita, Y.; Naito, H.; Sugimura, K. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: CT and MR angiographies have been reported to visualize the artery of Adamkiewicz (AKA) noninvasively to prevent spinal cord ischemia in surgery of thoracic descending aortic aneurysms. The purpose of this work was to compare the usefulness of CT angiography (CTA) with intra-arterial contrast injection (IACTA) with that of conventional CTA with intravenous contrast injection (IVCTA).MATERIALS AND METHODS: We enrolled 32 consecutive patients with thoracic or thoracoabdominal aortic aneurysms who were scheduled for surgical repair or endovascular stent-graft treatment. All of the CTA images were obtained using a 16-detector row CT scanner and 100 mL of contrast material (370 mg/mL) injected at a rate of 5 mL/s. Contrast was injected via the antecubital veins of 15 patients and via a pig-tail catheter placed at the proximal portion of the descending aorta in 17 patients who underwent IVCTA and IACTA, respectively. Two datasets were reconstructed from 2 consecutive scans. The AKA was identified as a characteristic hairpin curved vessel in the anterior midsagittal surface of the spine and by the absence of further enhancement in the second rather than in the first phase. Continuity between the AKA and aorta was confirmed when the vessel could be traced continuously by paging the oblique coronal multiplanar reconstruction or original axial images.RESULTS: Intra-arterial contrast injection was significantly more sensitive in identifying the AKA than IVCTA: 16 (94.1%) of 17 versus 9 (60.0%) of 15 (P = .033). Continuity between the AKA and aorta through intercostal or lumbar artery was confirmed in 14 (87.5%) of 16 and 5 (55.6%) of 9 of the IACTA and IVCTA groups, respectively.CONCLUSION: Intra-arterial contrast injection detected the AKA at a high rate and verified continuity from the aorta to the AKA.